2006
DOI: 10.1021/jp063078w
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Folding Dynamics:  A Time-Resolved Study from the Nanosecond to the Microsecond Time Regime

Abstract: Time-resolved spectroscopies, spanning from the nanosecond to the microsecond time regime, coupled with molecular mechanics calculations, allowed us to assess the most populated conformations in solution of a series of analogues of trichogin GA IV, a natural undecapeptide showing significant antimicrobial activity. This peptide is characterized by a high content of the conformationally constrained alpha-aminoisobutyric acid and by a glycine-glycine motif in the central part of the sequence. Nanosecond time-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…It has already been reported that while substitution of the Fmoc group does not affect the conformational properties of the trichogin analogues, inclusion of TOAC in the C-terminal segment slightly stabilizes the helical conformation. [15] Permeabilization experiments on phospholipid bilayers proved that the above substitutions do not perturb the membrane activity of the peptides investigated. [14] The metal ion binding properties of two fluorescent analogues of trichogin GA IV, which is a natural undecapeptide showing significant antimicrobial activity, were studied by circular dichroism, time-resolved optical spectroscopy, and molecular mechanics calculations.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…It has already been reported that while substitution of the Fmoc group does not affect the conformational properties of the trichogin analogues, inclusion of TOAC in the C-terminal segment slightly stabilizes the helical conformation. [15] Permeabilization experiments on phospholipid bilayers proved that the above substitutions do not perturb the membrane activity of the peptides investigated. [14] The metal ion binding properties of two fluorescent analogues of trichogin GA IV, which is a natural undecapeptide showing significant antimicrobial activity, were studied by circular dichroism, time-resolved optical spectroscopy, and molecular mechanics calculations.…”
Section: Introductionmentioning
confidence: 89%
“…[14,15] It has been shown that for Fmoc···TOAC centre-tocentre distances longer than 4-5 , the Fçrster dipole-dipole interaction model [27] adequately describes the excited state interaction between the aromatic molecule and the nitroxyl radical quencher. [28] At shorter distances, the overlap of the electronic distributions gives rise to ultrafast relaxation mechanisms that completely deplete the fluorescence emission.…”
Section: Fluorescence Experimentsmentioning
confidence: 99%
See 3 more Smart Citations